INTEGRASI LANDASAN FILOSOFIS, TEOLOGIS, DAN PEDAGOGIS DALAM TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KONTEMPORER - Yulia Wahyuni; Lia Laili Rosadah; Abdurrahmansyah; Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of philosophical, theological, and pedagogical foundations in the transformation of contemporary Islamic Religious Education (PAI) learning forms the central focus of this study. Social changes, the rapid development of digital technology, and the demands of 21st-century competencies have positioned PAI not merely as a process of transferring religious knowledge, but also as a systematic effort to develop character, strengthen spiritual literacy, and foster students’ critical thinking skills. This study employs a qualitative approach using a library research method, analyzing various scholarly works related to the philosophy of Islamic education, theological sources, and modern learning theories. The findings indicate that the philosophical foundation determines the direction of forming the concept of insan kamil based on the principle of tawhid. The theological foundation ensures that the substance of learning is grounded in the Qur’an and Hadith, while the pedagogical foundation provides systematic, contextual, and student-centered learning strategies. The integration of these three foundations produces a transformative model of Islamic Religious Education learning that is adaptive to contemporary dynamics while remaining firmly rooted in divine values. Therefore, the synergy of philosophical, theological, and pedagogical foundations becomes a strategic basis for developing Islamic Religious Education learning that is relevant, humanistic, and sustainable.